Obesity, weight loss and health-related quality of life - Rissanen, Aila; Kaukua, Jarmo (Henry Stewart Talks, 2007)
Obesity: research and clinical practice, Quality of life: functioning and wellbeing, Physical, mental, social and obesity-specific perspectives, Health-related quality of life (HRQOL), Questionnaires, Disease-specific measure of HRQOL, Obesity specific HRQOL questionnaires, Psychosocial problems, Evidence from population studies, Weight and physical functioning, Weight change and HRQOL, Medical complications of obesity, Evidence from weight loss studies, The paradox of health-care, Pharmacotherapy and HRQOL, Surgical procedures